Riesgos naturales y su impacto en el tramo Caldera-Puntarenas, ferrocarril al Pacífico, Costa Rica (1900-1930) - Zúñiga Arias, Ana Yolanda (Revista de historia., 2017)
The article analyzed from historically and geographically, the impact of natural hazards on the railway to the Pacific section between Caldera and Puntarenas, Costa Rica from 1900 to 1930. Taking into account three elements that directly impact the area: landslides, tidal and river overflows Barranca. The analysis is based on primary sources including documents from the National Archive of Costa Rica, period photographs and national newspapers.